AKULTURASI BUDAYA SOSIAL DAN MAKNA SIMBOLIK TARI DERO - Andi Imrah Dewi; Andi Febri Herawati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
The process of acculturation runs very quickly or slowly depending on the perception of the local community towards the incoming foreign culture. The purpose of the study is to find out the cultural acculturation and symbolic meaning of dero dance. Research methods use a qualitative approach, with a single case study design. Data collection techniques through observation, interviews, and documentation studies. The results of the study that dero dance has a common meaning as a form of gratitude and a sense of community unity regardless of social strata but the meaning and value shifted due to the acculturation of foreign cultures using modern music collaborated with other cultures. The special meaning of the dero dance movement is a simple and simultaneous presentation of motion in doing and has its attraction that can give suggestions and feel the desire of everyone to participate in doing dero dance moves. This type of dance is a popular traditional dance that can be followed and pulled with the whole community in the event of a traditional party and dero dance is a social dance from various circles considering that this dero dance aims to unite the movement. Dero dance is performed at the traditional ceremony of the wedding and thanksgiving party. The meaning of the floor pattern of the circle shape that is not broken and well maintained as a form of mutual help.